BosR: A novel biofilm-specific regulator in Pseudomonas aeruginosa - Dostert, Melanie; Belanger, Corrie R.; Pedraz, Lucas; Alford, Morgan A.; Blimkie, Travis M.; Falsafi, Reza F.; Bains, Manjeet; Dhillon, Bhavjinder Kaur; Haney, Cara H.; Lee, Amy H.; Hancock, Robert E. W. (Frontiers in Microbiology, 2022)
Biofilms are the most common cause of bacterial infections in humans and notoriously hard to treat due to their ability to withstand antibiotics and host immune defenses. To overcome the current lack of effective antibiofilm therapies and guide future design, the identification of novel biofilm-specific gene targets is crucial. In this regard, transcriptional regulators have been proposed as promising targets for antimicrobial drug design. Therefore, a Transposon insertion sequencing approach was employed to systematically identify regulators phenotypically affecting biofilm growth in Pseudomonas aeruginosa PA14 using the TnSeq analysis tools Bio-TraDIS and TRANSIT. A screen of a pool of 300,000 transposon insertion mutants identified 349 genes involved in biofilm growth on hydroxyapatite, including 47 regulators. Detection of 19 regulatory genes participating in well-established biofilm pathways validated the results. An additional 28 novel prospective biofilm regulators suggested the requirement for multiple one-component transcriptional regulators. Biofilm-defective phenotypes were confirmed for five one-component transcriptional regulators and a protein kinase, which did not affect motility phenotypes. The one-component transcriptional regulator bosR displayed a conserved role in P. aeruginosa biofilm growth since its ortholog in P. aeruginosa strain PAO1 was also required for biofilm growth. Microscopic analysis of a chromosomal deletion mutant of bosR confirmed the role of this regulator in biofilm growth. Overall, our results highlighted that the gene network driving biofilm growth is complex and involves regulators beyond the primarily studied groups of two-component systems and cyclic diguanylate signaling proteins. Furthermore, biofilm-specific regulators, such as bosR, might constitute prospective new drug targets to overcome biofilm infections.